Cerebrometabolic Health - Мarine М. Tanashyan; Antonova V. Antonova (Анналы клинической и экспериментальной неврологии)
The article addresses the global challenge of nervous system damage and cerebral consequences in metabolic disorders. It introduces the concept of impaired cerebral metabolic health as a progredient progression of cerebral dysfunction. Delineating the sequence of changes at all stages underscores the importance of targeted timely interventions to ensure preventive measures and treatment of cerebral vascular diseases.